(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Neurodegenerative disorders have rung the alarming bell with their burgeoning prevalence and global burden. Mild Cognitive Impairment (MCI) is turning out as a global epidemic of severe concern for developing and low-income economies like ours. India ranked third in the world for having a huge number of people with dementia. MCI is the transitional phase between normal aging process and Alzheimer’s disease. Being insidious in nature, its early detection through neuropsychological testing procedure is of utmost importance and if undiagnosed it may lead to irreversible diseases such as Alzheimer’s. Hence, to tackle the menace being imposed by MCI, the scientific groups have devised novel therapeutic approaches to counteract the ever increasing epidemic of MCI and complications associated with. In the current scenario, role of vitamin B12 in improving cognition levels in the geriatric population is gaining wide impetus. Scientific reports have proposed that vitamin B12 supplementation has shown protective effect in treatment of neurological disorders. With these findings providing strong basis, the vitamin B12 might enhance cognitive functions and maintain the overall brain health. Secondly, flaxseeds amongst the prime functional food are the need-of-the-hour. Flaxseeds are a potent source of omega-3 fatty acids, most significantly alphalinolenic acid (ALA). It has shown to provide risk modulation against neurological disorders notably Alzheimer’s disease, dementia, etc, cardiovascular benefits, beneficial changes in blood lipid profile, protection against some types of cancer and many more.